Analysis of the Contribution of the Agricultural Sector to the GRDP Value of Dairi Regency, North Sumatra Province - Marliyah, Marliyah; Syahbudi, Muhammad; Limbong, Lisna (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The agricultural sector in Dairi Regency is a strategic sector that has close links with poverty reduction, efforts to overcome unemployment, efforts to build food security, food production, environmental conservation efforts and the basis of regional economic development. the distribution of the highest percentage of Gross Regional Domestic Product (GRDP) from 2014-2018 compared to other sectors. This study aims to examine how big the contribution of the agricultural sector to the Gross Regional Domestic Product (GRDP) in Dairi Regency and to find out how big the projected growth of the agricultural sector's contribution in 2025 in Dairi Regency is with quantitative research using secondary data. This study uses time series data in the form of annual data with a time span of 2016-2020. Data were analyzed using contribution analysis and least squared trend analysis (least square method). Process data processing using excel software. The results of the contribution analysis show that the contribution of the agricultural sector to the Gross Regional Domestic Product (GDP) of Dairi Regency in 2016 was 46.02%, in 2017 it was 45.68%, in 2018 it was 45.29%, in 2019 it was 44.79%, and in 2020 by 45.19%. The results of the analysis of the least squares trend (least square method) show the projected growth of the contribution of the agricultural sector to the Gross Regional Domestic Product (GDP) of Dairi Regency in 2021 by 44.63%, in 2022 by 44.37%, in 2023 by 44.12%, in 2024 by 43.86% and in 2025 by 43.61%.